Headaches and obesity - Fortini, Ida; Felsenfeld, Bernardo Dror, Junior (Arquivos de Neuro-Psiquiatria, 2022)
Obesity and headache disorders are two very common conditions in the general population that have been increasing in incidence over the last decades. Recent studies have shown a significant relationship between obesity and headaches, particularly migraine, with an important role in whether the disease is chronic. On the other hand, no such association was found with tension-type headaches. Studies showing an overlapping of hunger-control pathways and those involved in the pathophysiology of migraine may justify the close association between obesity and migraine. Moreover, a secondary headache for which obesity is a strong risk factor is idiopathic Intracranial Hypertension (pseudotumor cerebri), with several studies showing the impact of weight reduction/bariatric surgery in the treatment of the disease. In conclusion, since obesity is a modifiable risk factor, it is important for physicians treating patients with headaches, and particularly migraine, to be aware of the association between these two disorders.
Keywords: Body Mass Index; Obesity; Headaches; Migraine without Aura; Pseudotumor Cerebri